KCNE Regulation of K+ Channel Trafficking – a Sisyphean Task? - Kanda, Vikram A.; Abbott, Geoffrey W. (Frontiers in Physiology, 2012)
Voltage-gated potassium (Kv) channels shape the action potentials of excitable cells and regulate membrane potential and ion homeostasis in excitable and nonexcitable cells. With forty known members in the human genome and a variety of homomeric and heteromeric pore-forming alpha subunit interactions, post-translational modifications, cellular locations and expression patterns, the functional repertoire of the Kv alpha subunit family is monumental. This versatility is amplified by a host of interacting proteins, including the single membrane-spanning KCNE ancillary subunits. Here, examining both the secretory and the endocytic pathways, we review recent findings illustrating the surprising virtuosity of the KCNE proteins in orchestrating not just the function, but also the composition, diaspora and retrieval of channels formed by their Kv alpha subunit partners.